2016
DOI: 10.1155/2016/1240843
|View full text |Cite
|
Sign up to set email alerts
|

GDF-15 and Hepcidin Levels in Nonanemic Patients with Impaired Glucose Tolerance

Abstract: Aims. Growth Differentiation Factor-15 (GDF-15) has been suggested as one of the regulators of hepcidin, an important regulatory peptide for iron deposition. Current data is conflicting about the relationship between hepcidin and disorders of glucose metabolism. We aimed to investigate serum hepcidin and GDF-15 concentrations and their associations with each other, in nonanemic subjects with impaired glucose tolerance (IGT) in comparison with the nonanemic subjects with normal glucose tolerance (NGT). Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Growth differentiation factor-15 (GDF-15), also called MIC-1 ( 40 ), is a member of the TGF-β superfamily that is up regulated in many cancers, including breast cancer ( 40 , 41 ). GDF-15 has previously been shown to correlate with and potentially regulate hepcidin, although in some contexts GDF-15 may act as an inhibitor rather than an activator of hepcidin (see Discussion and ( 42 – 45 )). We observed that GDF-15 was increased in our breast cancer cell models when compared to non-cancer cells: MCF-7 spheroids had increased GDF-15 compared to MCF-10A spheroids, as did patient tumor spheroids compared to spheroids derived from normal adjacent cells ( Figure 5A and B ).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Growth differentiation factor-15 (GDF-15), also called MIC-1 ( 40 ), is a member of the TGF-β superfamily that is up regulated in many cancers, including breast cancer ( 40 , 41 ). GDF-15 has previously been shown to correlate with and potentially regulate hepcidin, although in some contexts GDF-15 may act as an inhibitor rather than an activator of hepcidin (see Discussion and ( 42 – 45 )). We observed that GDF-15 was increased in our breast cancer cell models when compared to non-cancer cells: MCF-7 spheroids had increased GDF-15 compared to MCF-10A spheroids, as did patient tumor spheroids compared to spheroids derived from normal adjacent cells ( Figure 5A and B ).…”
Section: Resultsmentioning
confidence: 93%
“…GDF-15 is induced in response to inflammation, acute injury or malignancy ( 41 , 55 , 56 ). Serum levels of both GDF-15 and hepcidin are increased in patients with breast cancer ( 6 , 41 ) and other malignancies ( 42 , 43 , 57 ). GDF-15 may play multiple roles in cancer; however, studies in breast cancer cells have suggested a role of GDF-15 in enhanced invasion as well as in maintenance of breast cancer stem cells ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…[11]. GDF-15, an anti-in ammatory cytokine, is a signi cant regulator of hepcidin and a strong positive correlation has been reported between them in anaemic patients [12,13]. In addition, Erythroblasts secrete GDF-15, which in turn suppresses hepcidin expression and decreases iron stores [14].…”
Section: Introductionmentioning
confidence: 99%
“…Growth Differentiation Factor-15 (GDF-15), an antiinflammatory cytokine, has been suggested as a significant regulator of hepcidin [11]. Oxidative stress and inflammatory conditions can stimulate secretion of GDF-15 by macrophages [12].…”
Section: Introductionmentioning
confidence: 99%